Telehealth Listening Visits for emotionally distressed mothers of hospitalized newborns: Proof-of-concept - Segre, Lisa S.; McCabe, Jennifer E.; Chuffo Davila, Rebecca; Arndt, Stephan (Frontiers in Psychiatry, 2022)
Problem. Newborn admission to the neonatal intensive care unit (NICU) is stressful. Yet in clinical practice, at best, NICU mothers are screened for depression and if indicated, referred to a mental-health specialist. At worst, no action is taken. Listening Visits, an empirically supported nurse-delivered intervention addressing emotional distress, can be conveniently provided by a NICU nurse. Prompted by the pandemic and the need to minimize face-to-face contacts, this manuscript describes the first evaluation of Listening Visits delivered over zoom. Material and Methods. Nine NICU mothers with mild to moderate depression symptoms received up to six Listening Visits sessions from a NICU nurse via zoom. Participants completed the Inventory Depression and Anxiety Symptoms-General Depression scale (IDAS-GD) at study entry and four- and eight- weeks post enrollment. They completed the Client Satisfaction Questionnaire (CSQ) at the 8-week assessment. Results. Using an intent-to-treat approach, the effect of time from the mixed model analysis of IDAS-GD was statistically significant (F(2,26)=10.50, p<.001), indicating improvement in IDAS-GD scores from baseline to follow-up. The average CSQ score was high (M=29.0, SD=3.3), with 75% of participants rating the quality of help they received as ‘excellent.” Discussion. In this pilot feasibility trial, we learned it is feasible to provide Listening Visits over zoom, that this mode of delivery is associated with a significant decrease in depression symptom scores, and that women valued this approach.